Asymmetric alloy formation at the Fe-on-Ti and Ti-on-Fe interfaces. (22nd October 2018) - Balogh, J; Süle, P; Bujdosó, L; Horváth, Z E; Kaptás, D; Kovács, A; Merkel, D G; Nakanishi, A; Sajti, Sz; Bottyán, L
Abstract: The Fe-on-Ti and Ti-on-Fe interfaces were studied experimentally by Mössbauer spectroscopy (MS), transmission electron microscopy (TEM) and x-ray reflectometry (XRR) on Ti/Fe/Ti trilayers grown on Si(1 1 1) substrates by vacuum evaporation. The nanoscale structure and composition were explored in cross sections using TEM, the layer structure and the interface widths by specular x-ray reflectometry. MS was applied to identify the interface alloy phases and to determine the pure and alloyed Fe layer fractions. The experimental results were compared with molecular dynamics (MD) simulations of layer growth on Fe or Ti underlayers of different orientations. The concentration distributions provided by MD simulations show an asymmetry at the interfaces in the layer growth direction. The transition is atomically sharp at the Ti-on-Fe interface for the (0 0 1) and (1 1 0) crystallographic orientations of the Fe underlayer, while it spreads over a few atomic layers for Fe(1 1 1) underlayer and for all studied Ti underlayer orientations at the Fe-on-Ti interface. MS and XRR data on Ti/Fe/Ti trilayers confirm the asymmetry between the bottom and top Fe interface, but the inferred interface widths considerable exceed those deduced from the MD simulations.